1997
DOI: 10.1055/s-2007-979516
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Representativity of Neuropsychiatrists and their Patients in a Drug Utilization Observation Study on Fluoxetine

Abstract: This study presents a methodological approach to an expost facto investigation of sample bias in drug utilization observation (DUO) studies using the example of a DUO with the nontricyclic antidepressant fluoxetine. A total of 479 psychiatrists and neurologists and 2,401 patients were investigated. The purpose of the study was to judge the representativeness of our DUO sample for two populations: first, for all psychiatrics and neurologists prescribing fluoxetine or all patients being treated with fluoxetine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Only physicians with patients on mirtazepine prescriptions were included, as the manufacturer wanted to improve drug treatment as part of the overall patient management. In similar studies, it has been shown that such sampling results in an overrepresentation of prescribers of the target drug [23], so that the resulting sample of physicians is prototypically representative for this group of physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Only physicians with patients on mirtazepine prescriptions were included, as the manufacturer wanted to improve drug treatment as part of the overall patient management. In similar studies, it has been shown that such sampling results in an overrepresentation of prescribers of the target drug [23], so that the resulting sample of physicians is prototypically representative for this group of physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies it was shown that, by this procedure, physicians are selected who have special expertise with the target drug (Schaaf et al, 1997). Although payment for documentation was low in comparison with medical reimbursement guidelines, this also could have influenced the decision to switch to amisulpride or how to evaluate the course of treatment, as it is also known even from controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…They were therefore not representative of all physicians but for the group of those who were experienced with this drug. 21 Patient selection or the mode of treatment were fully left to the discretion of the physicians as this was a prerequisite for studying the routine treatment and especially routine dosages. Treatment of 692 patients was recorded, that is 71.6% females and 28.4% males.…”
Section: Methodsmentioning
confidence: 99%